The Impact on Digital Marketing: An Overview (International Journal of Innovative Research in Engineering & Management, 2021)
In the last decade, the numbers of advanced learning foundations  in the Indonesia, both governmental and private, has increased.  With this level of competition, it's more important than ever for  schools to figure out how to stands out also effectively promote  themselves for incoming student. The importance of  computerized media as a commercial platform is well  recognized at this time, and schools are increasingly embracing  web-based advertising channels over traditional ones. The  primary goal of this research study is to figure out how  understudies use advanced media and, more specifically, what  role the media plays in the dynamic cycle of selecting a college.  This data on the use of computerized promoting in Higher  Educations Institutions (HEIs), especially as part of college  promoting methods, is very important to compete for competent  understudies all together. The purpose of article is look into  influence of the higher education foundations computerized  advertising on the dynamic cycle of understudies. This study  used a subjective research method, using semi-organized  meetings, perception, and documentation as information  gathering tools.
Keywords: College; Digital; Education; Marketing; Student